2016
DOI: 10.3390/s16060827
|View full text |Cite
|
Sign up to set email alerts
|

Local Strategy Combined with a Wavelength Selection Method for Multivariate Calibration

Abstract: One of the essential factors influencing the prediction accuracy of multivariate calibration models is the quality of the calibration data. A local regression strategy, together with a wavelength selection approach, is proposed to build the multivariate calibration models based on partial least squares regression. The local algorithm is applied to create a calibration set of spectra similar to the spectrum of an unknown sample; the synthetic degree of grey relation coefficient is used to evaluate the similarit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Although PLS and PCR address some of the issues that rise from the large p , small n nature of spectroscopic data, it has been shown that the inclusion of uninformative wavelengths in the training process negatively affects the accuracy of predictions as well as model interpretability [19][20][21][22]43 . Moreover, from a more practical point of view, the identification of the specific wavelengths, or regions of the optical spectrum, that contain information about chemical species, significantly reduces the time and cost associated with monitoring them and facilitates the development of portable, high-speed sensors.…”
Section: Wavelength Selectionmentioning
confidence: 99%
“…Although PLS and PCR address some of the issues that rise from the large p , small n nature of spectroscopic data, it has been shown that the inclusion of uninformative wavelengths in the training process negatively affects the accuracy of predictions as well as model interpretability [19][20][21][22]43 . Moreover, from a more practical point of view, the identification of the specific wavelengths, or regions of the optical spectrum, that contain information about chemical species, significantly reduces the time and cost associated with monitoring them and facilitates the development of portable, high-speed sensors.…”
Section: Wavelength Selectionmentioning
confidence: 99%
“…The optimal wavelength selection offers two clear benefits. Firstly, it has been shown that the inclusion of uninformative wavelengths in the training process negatively affects the accuracy of predictions and model interpretability [ 48 , 49 ]. Secondly, from a more practical point of view, the identification of a few wavelengths, or regions of the optical spectrum, that contain information about chemical species, significantly reduces the time and cost associated with their measurement and enables the development of portable and high-speed optical sensors.…”
Section: Resultsmentioning
confidence: 99%
“…Reducing dimensions and seeking the most informative wavelengths are effective methods for processing data while selecting the most informative wavelengths of target information is an effective measure to simplify computation and improve the model performance (Li et al, 2019 ; Zhou et al, 2020 ). First, it has been shown that the inclusion of uninformative wavelengths while modeling affects the performance of predicting or classifying and model interpretability (Chang et al, 2016 ). Second, the identification of wavelengths that contain information about the attribute the research focuses on, will reduce the computation time and cost, from a more practical point of view (Zhang et al, 2019 ; Mamouei et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%